Robert Ludlum's the Bourne retribution [compact disc, unabridged] : a new Jason Bourne novel - Lustbader, Eric (Lustbader, Eric. New Jason Bourne novel., 2013)
"When Director Yadin learns of a mysterious connection between Ouyang Jidan, a senior member of China's Politburo, and a recently deceased Mexican drug lord, he asks Jason Bourne to investigate." -- Provided by the publisher.